2012
DOI: 10.1016/j.pubrev.2012.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Public relations in Kenya: An exploration of models and cultural influences

Abstract: This pioneer study explores the public relations models that inform the practice of public relations in Kenya, and the cultural values that influence this practice. Results show the personal influence model as the most used by practitioners in Kenya, while individualism is the most experienced cultural value. The strong correlation between personal influence model and Hofstede's cultural value of femininity points to the practitioners' strong desire for good interpersonal relationships with colleagues, supervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 8 publications
3
11
0
Order By: Relevance
“…Their study suggested that although two-way communication (symmetrical and asymmetrical) is practiced, PR in Ghana is largely shaped by the personal influence and cultural interpreter models. Other scholars such as Kiambi (2012), Oskiutycz and Enombo (2011), and Anani-Bossman (2019) have made similar findings in Kenya, Gabon and Ghana respectively.…”
Section: Literature Reviewsupporting
confidence: 60%
See 1 more Smart Citation
“…Their study suggested that although two-way communication (symmetrical and asymmetrical) is practiced, PR in Ghana is largely shaped by the personal influence and cultural interpreter models. Other scholars such as Kiambi (2012), Oskiutycz and Enombo (2011), and Anani-Bossman (2019) have made similar findings in Kenya, Gabon and Ghana respectively.…”
Section: Literature Reviewsupporting
confidence: 60%
“…The authors contend that most of the developments in public relations theories and research conducted are mainly from Western perspectives. In Africa, some attempts have been made to address this imbalance (Kiambi, 2012; Oksiutycz and Enombo, 2011, Thompson, 2018; Wu and Baah-Boakye, 2006, 2009). In Ghana, Thompson (2018), for instance, conducted a study on PR education in an emerging democracy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Petersone (2004) describes that press-agentry is the most considerable model influenced by economic and political situations in Latvia. In Kenya, two-way symmetrical is in the first position, followed by press-agentry, two-way asymmetrical, and public information (Kiambi and Nadler, 2012).…”
Section: Government Public Relations and Democracy In Indonesiamentioning
confidence: 99%
“…In the government institutions, there is little appreciation of the role played by Public Relations tools in sensitizing the public on government projects (Kiambi, 2010). This is evidenced by the fact that public relations officers are not part of the top management teams that make decisions including policies and regulations that would need to be communicated to the public.…”
Section: Statement Of the Problemmentioning
confidence: 99%